Comment: Foreign Contracts and U.S. Copyright Termination Rights: What Law Applies? - Arnold, Richard; Ginsburg, Jane (The Columbia Journal of Law & the Arts, 2020)
The U.S. Copyright Act gives authors the right to terminate assignments of copyrights in works other than works for hire, executed on or after January 1, 1978, after thirty-five years, and to do so notwithstanding any agreement to the contrary. Given that agreements which are subject to the laws of other countries can assign U.S. copyrights, and purport to do so in perpetuity, U.S. law’s preclusion of agreements contrary to the author’s right to exercise her termination right can give rise to a difficult choice of law issue. Two recent cases which came before courts in the U.S. and England respectively, Ennio Morricone Music Inc. v. Bixio Music Group Ltd. and Gloucester Place Music Ltd v. Le Bon illustrate the problem. In neither case was the choice of law question disputed by the parties, and hence neither court had occasion fully to analyze it. Nevertheless, the Court of Appeals for the Second Circuit in the Morricone case made an observation about the nature of U.S. copyright which has a potentially important bearing on the matter. In this article we consider the choice of law issue from the perspectives of U.S. law and English law. Under either law, the key question is what law governs the permissible scope of an author’s grant. Given that copyright is territorial, as a matter of principle, one would expect that law to be the lex loci protectionis, and that is essentially what both U.S. law and English law stipulate. Where the copyright is a U.S. copyright, application of the lex loci protectionis in accordance with the conceptualization suggested by Morricone, concerning the inalienable character of the right, leads to the conclusion that § 203 cannot be overridden by a contract subject to a different law. We do not conclude, however, that a multinational grant will incorporate every national law limitation on the scope of the grant. Limits on the scope of the grant which are substantive, when characterized in accordance with the lex loci protectionis, must be given effect, but not limits which are evidential or procedural.